Wave-induced extreme water levels in the Puerto Morelos fringing reef lagoon - Torres-Freyermuth, A.; Mariño-Tapia, I.; Coronado, C.; Salles, P.; Medellín, G.; Pedrozo-Acuña, A.; Silva, R.; Candela, J.; Iglesias-Prieto, R. (Natural hazards and earth system sciences, 2012)
Wave-induced extreme water levels in the Puerto Morelos fringing reef lagoon are investigated by means of a phase-resolving non-hydrostatic wave model (SWASH). This model solves the nonlinear shallow water equations including non-hydrostatic pressure. The one-dimensional version of the model is implemented in order to investigate wave transformation in fringing reefs. Firstly, the numerical model is validated with (i) laboratory experiments conducted on a physical model (Demirbilek et al., 2007)and (ii) field observations (Coronado et al., 2007). Numerical results show good agreement with both experimental and field data. The comparison against the physical model results, for energetic wave conditions, indicates that high- and low-frequency wave transformation is well reproduced. Moreover, extreme water-level conditions measured during the passage of Hurricane Ivan in Puerto Morelos are also estimated by the numerical tool. Subsequently, the model is implemented at different along-reef locations in Puerto Morelos. Extreme water levels, wave-induced setup, and infragravity wave energy are estimated inside the reef lagoon for different storm wave conditions (Hs >2 m). The numerical results revealed a strong correlation between the offshore sea-swell wave energy and the setup. In contrast, infragravity waves are shown to be the result of a more complex pattern which heavily relies on the reef geometry. Indeed, the southern end of the reef lagoon provides evidence of resonance excitation, suggesting that the reef barrier may act as either a natural flood protection morphological feature, or as an inundation hazard enhancer depending on the incident wave conditions.